The effects of eider husbandry on the behaviour and nesting success of the common eider (Somateria mollissima) in the Westfjords of Iceland - Murray, Julia Lindsay, 1976- (2018)
Whilst eider husbandry for down collection in Iceland is commonly considered sustainable, there is no consensus amongst farmers on optimum methods for minimising impacts of disturbance to the eiders whilst maximising yield of quality down. Disturbance to wild birds can in some circumstances lead to decreased breeding success, usually associated with increased predation levels where nests have been left unattended. This thesis investigates the response of nesting eiders to farmers' activities during early and late incubation, in relation to variables such as degree of vegetative nest cover and use of artificial nest shelters. The effect on nest predation levels as a result of these activities is then assessed. Incubating eiders were observed during nest marking and down collection sessions at five colonies in Iceland's Westfjords. Degree of response and time away from the nest were recorded, and whether the bird was 'adjacent', i.e. merely walked past, or 'targeted' for marking or down collection. Each farmer's differing approach and behaviour whilst in their colony was also observed. Eiders' responses varied depending on predictability of the farmer's approach. During early incubation target birds flushed more frequently, and whilst eiders with the protection of shelters flushed from greater distances, they returned significantly sooner than non-shelter birds (p=0.03), suggesting that these are coveted nest sites before vegetation begins to grow. During late incubation, eiders nesting in exposed sites where the eggs would be more vulnerable, took shorter incubation recesses than those at least partially concealed by vegetative cover (p=0.01). The predation level was low in all nest types however, likely due to sustained predator control efforts across the area, so the effect on nesting success of increased recesses and human presence was negligible. Eider husbandry activities in this region thus do not have a negative impact on productivity, but the eiders' responses differed with the varying husbandry practices ...